Evolutionary persistence of tripartite integrative and conjugative elements - Haskett, T.; Ramsay, Joshua; Bekuma, A.; Sullivan, J.; O'Hara, G.; Terpolilli, J. (2017)
Integrative and conjugative elements (ICEs) are generally regarded as regions of contiguous DNA integrated within a bacterial genome that are capable of excision and horizontal transfer via conjugation. We recently characterized a unique group of ICEs present in Mesorhizobium spp., which exist as three entirely separate but inextricably linked chromosomal regions termed a, ß and ?. These regions occupy three different recombinase attachment (att) sites; however, they do not excise independently. Rather, they recombine the host chromosome to form a single contiguous region prior to excision and conjugative transfer. Like the single-part ICE carried by M. loti R7A (ICEMlSym R7A ), these “tripartite” ICEs (ICE 3 s) are widespread throughout the Mesorhizobium genus and enable strains to form nitrogen-fixing symbioses with a variety of legumes. ICE 3 s have likely evolved following recombination between three separate ancestral integrative elements, however, the persistence of ICE 3 structure in diverse mesorhizobia is perplexing due to its seemingly unnecessary complexity. In this study, examination of ICE 3 s revealed that most symbiosis genes are carried on the large a fragment. Some ICE 3 -ß and ? regions also carry genes that potentially contribute to the symbiosis, or to persistence in the soil environment, but these regions have been frequently subjected to recombination events including deletions, insertions and recombination with genes located on other integrative elements. Examination of a new ICE 3 in M. ciceri Ca181 revealed it has jettisoned the genetic cargo from its ß region and recruited a serine recombinase gene within its ? region, resulting in replacement of one of the three ICE 3 integration sites. Overall the recombination loci appear to be the only conserved features of the ß and ? regions, suggesting that the tripartite structure itself provides a selective benefit to the element. We propose the ICE 3 structure provides enhanced host range, host stability and resistance to destabilization by tandem insertion of competing integrative elements. Furthermore, we suspect the ICE 3 tripartite structure increases the likelihood of gene capture from integrative elements sharing the same attachment sites.